Effectiveness of Local Microorganisms from Glysine max Dregs in Formulation with Coconut Milk and Degan Coconut Water as a Test for the Effect of Ultisol Soil Fertility - Erwin Junaidi Lubis (CV Projurnal Mitra Publikasi, 2025)
The application of a mixture of Coconut Milk and Degan Coconut Water formulated with Glysine max Dregs can improve the fertility and health of Ultisol soils which are nutrient deficient or nutrient poor in Ultisol soils. The use of the three ingredients has important potential as the effectiveness of soil fertility, and the impact on soil health. Glysine max dregs contains rich nutrients, namely nitrogen (N), phosphorus (P), and potassium (K), while coconut milk contains important nutrients and growth hormones that can refer to both plant growth, while Degan coconut water also contains rich nutrients, and also contains cytokinin hormones which play an important role in stimulating cell division and plant root growth. The conclusion is that Glysine max dregs, coconut milk and Degan coconut water can potentially increase the fertility of Ultisol soil and can create liquid organic fertilizer as an environmentally friendly and effective fertilizer in applying to soil and plants.